Plerixafor is effective given either preemptively or as a rescue strategy in poor stem cell mobilizing patients with multiple myeloma - Cheng, Jian; Schmitt, Michael; Wuchter, Patrick; Buß, Eike Christian; Witzens-Harig, Mathias; Neben, Kai; Hundemer, Michael; Hillengaß, Jens; Goldschmidt, Hartmut; Ho, Anthony Dick; Schmitt, Anita (Transfusion, 2015)
Background: Harvest of more than one CD34+ stem cell transplant has become the standard, to ensure the option for a second autologous transplantation in patients with relapsed or progressive multiple myeloma (MM). Additional administration of the CXCR-4 inhibitor plerixafor has been shown to increase the efficiency of CD34+ stem cell harvest. However, the algorithm when to apply plerixafor is still under debate. Study Design and Methods. In this retrospective study, 46 MM patients were categorized into four groups according to their CD34+ stem cell count in peripheral blood (PB) and mobilization with or without plerixafor: Group A comprised poor mobilizers with CD34+ cell counts of fewer than 20 × 106/L in PB. Group B included inadequate mobilizers with CD34+ cell counts of 20 × 106/L or more in PB and a low CD34+ stem cell yield in the first leukapheresis session. Patients receiving plerixafor preemptively (Group A1) and as a rescue strategy (Group B1) were compared to patients continuing stem cell collection with granulocyte-colony-stimulating factor alone (Groups A2 and B2). Results: In both, the preemptive and the rescue settings, plerixafor enhanced the CD34+ stem cell yield significantly. Poor mobilization and administration of plerixafor was not associated with delayed engraftment. Conclusion: Our data demonstrate that administration of plerixafor is safe and effective and facilitates a significantly higher CD34+ stem cell harvest. Based on the presented data, we propose an algorithm for the use of plerixafor for CD34+ stem cell mobilization and harvesting in poor mobilizing myeloma patients.